PUBLIC EMPLOYMENT AIMED AT THE DEVELOPMENT OF THE SOCIAL SPHERE ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
This scientific article explores the concept and impact of public employment programs on the development of the social sphere. In an era characterized by growing social challenges and economic disparities, governments across the globe are increasingly turning to public employment initiatives as a means to address these issues. This article reviews the objectives, design, and outcomes of such programs, shedding light on their effectiveness in promoting social development, improving well-being, and fostering economic stability. By analyzing case studies and empirical evidence, this article contributes to the understanding of the role of public employment in enhancing the social sphere and offers insights into potential policy recommendations.